Kinetic fractionation of copper and cadmium from soil model compounds - Varrault, G.; Fabre, Y.; Bermond, A. (Canadian Journal of Analytical Sciences and Spectroscopy, 2001)
The chemical speciation of soil trace elements corresponds to the use of chemical reagents in order to extract metallic cations from a soil sample. Usually, the quantification of the extracted metals in the solution is performed when equilibrium is reached. This work is more particularly devoted to the application of a kinetic fractionation of trace elements (copper, cadmium) to spiked (Cd, Cu) model compounds such as humic acids and goethite, which are well known to adsorb metallic cations in soils. When using EDTA as a chemical reagent, the kinetic fractionation described in this work provides two fractions called, respectively, labile and slowly labile. Its application to model compounds has shown that copper and cadmium bound to goethite are in a rather labile form while these cations bound to humic acids are more likely in a slowly labile form. Moreover, this fractionation method has been applied to mixtures of goethite and humic acids; the resulting changes in the proportion of labile and slowly labile forms have been determined.